Training needs of kindergarten teachers (4-5) years from their point of view (Journal of Hama University, 2019)
This research aims at exploring :The training needs of kindergarten teachers for (4-5) years from their point of view.For this reason, the questionnaire is applied to the sample. The sample is selected as follows :• The kindergartens are randomly selected in Damascus.• The sample of parameters is randomly selected from the parameters of the third category of age (4-5) years, reaches (73) parameter The results showed:-There are no statistically significant differences at the level of significance (0.05) between the average grades of training needs of kindergarten teachers for the discovery strategy in the development of scientific concepts due to the variable (scientific qualification.( -There are  no statistically significant differences at the level of significance (0.05) between the average grades of training needs of kindergarten teachers for the discovery strategy in the development of scientific concepts due to the variable (experiencee.(